Pengembangan Media Pembelajaran Komik Fisika Digital Berbasis Line Webtoon Pada Pokok Bahasan Tekanan - Diah Setiani; Putri Fathiya Artha Dewi; Savithri Maurizki Delya; Vera Rahmawati; Dasmo Dasmo (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
This research is based on the lack of learning media to support the learning process that can increase students' interest and motivation in learning physics. This study aims to produce a Line Webtoon-based digital physics comic learning media with the subject of pressure. The research method used is research and development (Research & Development) with reference to the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Data collection technique use in the form of charging poll through the Google Form, while the research instrument used includes a student needs charging poll consisting of 50 SMP Class VIII students randomly representing one province namely Central Java and a validation sheet consisting of material experts and media expert validation sheets. given to 6 (six) validators, namely 2 (two) material experts, 2 (two) media experts and 2 (two) linguists. This study shows that the results of the validation carried out by material experts, media experts, and linguists obtained an average percentage value of 93.81% in the very good category. Based on the results of research and discussion, it can be said that Line Webtoon-based digital comics are feasible to be implemented in physics learning.Keywords: Learning Media, Digital Comic, Line Webtoon, Physics, Pressure